Pengembangan Sistem Aplikasi berbasis Web Kolaborasi Pelaku UMKM dengan DISKOPERINDAG Kota Batu dalam Pemasaran Produk UMKM Kepada Masyarakat - Moch. Vicky Al Hidayah; Adam Hendra Brata; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
DISKOPERINDAG Batu City is a department that supervises and trains MSME actors in Batu City. MSME actors are a person or group of people who have a business that can be in the form of products or services. MSME actors here are limited to 2 types, MSME actors who have products and have shops or places to buy and sell. However, DISKOPERINDAG has difficulty in conducting supervision and training, due to lack of data and the amount of effort or costs that incurred. MSME actors in Batu City also experiencing difficulties in product marketing because there is no supporting media. With this problem, a web-based application system was created. Collaboration between the department and MSME actors to facilitate the work of DISKOPERINDAG in supervising and training MSME actors, as well as to assist MSME actors, product owners and shop owners to work together in developing businesses. This system was created by applying the SDLC waterfall method. The web-based system was chosen because it can be accessed through various platforms. In the requirements analysis process, the functional requirements and non-functional requirements are obtained as well as temporary prototype designs. The design is built using sequence diagrams, class diagrams, conceptual data model (CDM), physical data model (PDM), and pseudocode. The implementation process uses the PHP language with object-based infrastructure and data storage using MySQL. The last process is testing which is done by 3 methods, unit, integration, and validation testing is done by blackbox testing technique.